Defects and anomalies in powder bed fusion metal additive manufacturing. Issue 2 (April 2022) - Mostafaei, Amir; Zhao, Cang; He, Yining; Reza Ghiaasiaan, Seyed; Shi, Bo; Shao, Shuai; Shamsaei, Nima; Wu, Ziheng; Kouraytem, Nadia; Sun, Tao; Pauza, Joseph; Gordon, Jerard V.; et al.
Highlights: Common defects and anomalies in powder bed fusion metal additive manufacturing. Formation mechanism and practical mitigation strategies are discussed. Defects/anomalies are classified as powder-related, processing-related, and post-processing related issues. Properties such as mechanical behavior and corrosion resistance of defective parts are discussed. Current challenges, gaps, and future trends are discussed. Abstract: Metal additive manufacturing is a disruptive technology that is revolutionizing the manufacturing industry. Despite its unrivaled capability for directly fabricating metal parts with complex geometries, the wide realization of the technology is currently limited by microstructural defects and anomalies, which could significantly degrade the structural integrity and service performance of the product. Accurate detection, characterization, and prediction of these defects and anomalies have an important and immediate impact in manufacturing fully-dense and defect-free builds. This review seeks to elucidate common defects/anomalies and their formation mechanisms in powder bed fusion additive manufacturing processes. They could arise from raw materials, processing conditions, and post-processing. While defects/anomalies in laser welding have been studied extensively, their formation and evolution remain unclear. Additionally, the existence of powder in powder bed fusion techniques may generate new types of defects, e.g., porosity transferring from powder to builds. Practical strategies to mitigate defects are also addressed through fundamental understanding of their formation. Such explorations enable the validation and calibration of models and ease the process qualification without costly trial-and-error experimentation.